Analisis Perbandingan Arus Jenuh Pada Pendekat Terlindung Simpang Diponegoro-Pilau-Nenas Dengan Metode MKJI Dan Time Slice: Analysis Of Comparison Protected Approaches On Diponegoro-Pilau-Nenas Intersection By IHCM And Time Slice Methods - Ndari, Sona; Puspasari, Nirwana; Akbar, Reza Zulfikar (Media Ilmiah Teknik Sipil, 2024)
Over time the number of vehicles has increased due to improved urban conditions. This affects the emergence of problems in the Palangka Raya urban transportation system, which has an impact on the performance of the road network, especially the performance of signalized intersections. The purpose of this research is to calculate the value of saturation current (S) using the IHCM 1997. In order to analyze the saturation flow and road performance on the Diponegoro - Pilau - Nenas approach, Primary data and Secondary data are required, Primary data includes intersection geometric data and traffic volume in green hours. While secondary data includes location maps and population. In analyzing the comparison of saturated flow refers to the IHCM 1997 and the Time Slice method. The results of the comparison analysis of saturated flow with IHCM 1997 and Time Slice method on each approach A, B, C, and D respectively are 12.64%, 27.52%, 14.94%, and 36.94%. Also obtained the highest DS value using the saturated flow value of IHCM 1997 and Time Slice method is on St. Pilau which is respectively 1.09 included in the level of service F, and 0.93 included in the level of service E, then from the results of this analysis can be known by using the results of the calculation of saturated flow of Time Slice method there is an increase in the value of Level of Service (LOS).